What is the evidence base for diagnosing hypertension and for subsequent blood pressure treatment targets in the prevention of cardiovascular disease? - Schwartz, Claire L. (BMC Med, 2015)
Diagnosing and treating hypertension plays an important role in minimising the risk of cardiovascular disease and stroke. Early and accurate diagnosis of hypertension, as well as regular monitoring, is essential to meet treatment targets. In this article, current recommendations for the screening and diagnosis of hypertension are reviewed. The evidence for treatment targets specified in contemporary guidelines is evaluated and recommendations from the USA, Canada, Europe and the UK are compared. Finally, consideration is given as to how diagnosis and management of hypertension might develop in the future.